Potensi Simpanan Karbon pada Tegakan Revegetasi Lahan Pasca Tambang PT Holcim Indonesia Tbk - Omo Rusdiana; Syidik Fahmi (Jurnal Silvikultur Tropika, 2020)
Global warming is a gradual increase in the average temperature of the Earth’s atmosphere caused by the increased volumes of greenhouse gases such as carbon dioxide, methane, and nitrous oxide. Greenhouse gases is trapped inside the atmosphere and caused UV radiation difficulty passing through Earth’s atmosphere, a processed is often referred to as the greenhouse effect. Reclamation and revegetation activities were expected could decrease the greenhouse effect. The aims of the research is to estimate total carbon stock in Pine Forest age 2005 or 11 years and 2012 or 4 years, and also to compare the result with former research in post mining revegetation site PT Holcim Indonesia Tbk. Biomass measurement of trees, poles, and saplings is conducted with non-destructive methods meanwhile biomass measurements of understorey, litter, and necromassa used destructive methods. The result showed that the value of biomass and carbon stock on the 2005 pine stand is acquired 75.31 tons/ha and 35.39 tons/ha. The value of the biomass and carbon stock on the 2012 pine stand is acquired 12.72 tons/ha and 5.98 ton/ha or increased from the previous year's measurement. Increasing of biomass content and carbon stocks is caused several factors such as increasing of diameter increment dan site quality. Keywords: biomass, carbon, reclamation